Comparison of lightweight and solid milling cutter capabilities - Hanzl, Pavel; Zetková, Ivana; Zetek, Miroslav (Manufacturing Technology Journal, 2020)
Milling is one of the oldest methods of metal machining. This technology has been developed over a long time. The last milestone is the use of composite materials for the construction of cutting tools. However, there are other pos-sibilities for improvement offered by new production methods such as Metal Additive Manufacturing. The paper deals with machining experiments using a lightweight milling cutter with a lattice structure. The results of machin-ing are compared to the capabilities of a solid milling cutter. The evaluated parameters are: cutting forces, blade wear and surface roughness of the workpiece. Based on these parameters, it was not possible to confirm the benefit of the lightweight version for machining.
Keywords: Milling Tool; Topological Optimization; Direct Melting Laser Sintering; Metal Additive Manufacturing